Endocrine side effects of immune checkpoint inhibitors - Cardona, Zulma; Sosman, Jeffrey A.; Chandra, Sunandana; Huang, Wenyu (Frontiers in Endocrinology, 2023)
Immune checkpoint inhibitors (ICIs) have increasingly been the mainstay of treatment for numerous malignancies. However, due to their association with autoimmunity, ICIs have resulted in a variety of side effects that involve multiple organs including the endocrine system. In this review article, we describe our current understanding of the autoimmune endocrinopathies as a result of the use of ICIs. We will review the epidemiology, pathophysiology, clinical presentation, diagnosis, and management of the most commonly encountered endocrinopathies, including thyroiditis, hypophysitis, Type 1 diabetes, adrenalitis, and central diabetes insipidus.